Birds of Lansdowne forest division and adjacent suburban landscapes, Garhwal Himalayas, Uttarakhand, India: Community structure and seasonal distribution - MOHAN KUKRETI; DINESH BHATT (Society for Indonesian Biodiversity, 2014)
Kukreti M, Bhatt D. 2014. Birds of Lansdowne forest division and adjacent suburban landscapes, Garhwal Himalayas, Uttarakhand, India: Community structure and seasonal distribution. Biodiversitas 15: 80-88. This study of bird species diversity aims at understanding the distribution patterns and structures of avifauna of the two forest ranges and adjoining suburban areas of the Lansdowne forest division, Uttarakhand, India. Data on the abundance and richness were collected by standardized Verner’s line transect method for two years (January 2011 to December 2012). A total of 216 species were recorded from the study area. Family Muscicapidae with 30 species was found to be dominant in the forest habitats, while family Corvidae with 10 species was found to be dominant in the suburban areas. Results indicate that the forests had more complex bird community structure in terms of higher species richness (8.95 vs 8.59), higher species diversity (0.085 vs 0.080) and more rare species (74 vs 15) as compared to urban habitats. Bird species richness (BSR) and bird species diversity (BSD) fluctuated across seasons but not across habitat types. In order to sustain avian diversity, it is recommended that anthropogenic disturbance should be reduced and traditional agroforestry should be developed in the study area.